2022
DOI: 10.1049/rsn2.12315
|View full text |Cite
|
Sign up to set email alerts
|

A new GM (1,1) model suitable for short‐term prediction of satellite clock bias

Abstract: Due to the sensitivity of spaceborne atomic clock to many factors, the variation law of satellite clock bias (SCB) can be regarded as a grey system. The GM (1,1) model is a most classical and basic model of grey system, which has been successfully applied in SCB prediction. Moreover, many improved models have been proposed and widely used in various forecasts since GM (1,1) was generated. However, the prediction performance of these models is not obviously improved compared with the classical models in clock b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…where a is the development coefficient representing the development trend of x (0) , and b is the grey action quantity reflecting the change relationship of x (0) [33]. Defining â = [a, b] T , which were estimated by the least squares method:…”
Section: Establishment Of Gm (11)mentioning
confidence: 99%
“…where a is the development coefficient representing the development trend of x (0) , and b is the grey action quantity reflecting the change relationship of x (0) [33]. Defining â = [a, b] T , which were estimated by the least squares method:…”
Section: Establishment Of Gm (11)mentioning
confidence: 99%
“…There are many methods that can be applied to such nonlinear and unsmooth time series modeling. The effectiveness and robustness of traditional modeling and forecast methods such as fitting and extrapolation, the Grey System Model (GM) [18], and Auto Regressive and Moving Average (ARMA) [19] have been proven. With the recent developments in machine learning, the application of machine learning algorithms to GNSS signal processing has received increasing attention [20].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant work has been published, for example, Li et al improved the generalization ability of the grey model using an improved particle swarm algorithm, achieving a 6-hour prediction error of better than 1.60 ns for the clocks of four global positioning system (GPS) satellites 25 . Tan et al proposed an improved grey model based on the new information theory 26 , which showed improved average prediction performance compared to the basic grey model. Literature 27 has also compared the grey and polynomial models.…”
mentioning
confidence: 99%